Republic of Korea Financial Sector Assessment Program : Detailed Assessment of Observance - IOSCO Objectives and Principles of Securities Regulation - International Monetary Fund; World Bank (World Bank, Washington, DC, 2014)
An assessment of the level of implementation of the IOSCO Objectives and Principles of Securities Regulation (IOSCO Principles) was conducted in the Republic of Korea (Korea) from April 3 to 19, 2013 as part of the IMF-World Bank Financial Sector Assessment Program (FSAP). The assessment was made by Eija Holttinen, Monetary and Capital Markets Department, IMF, and Andrea Corcoran, an external expert working for the World Bank. The previous IOSCO assessment of Korea was conducted in 2001-02 before the first IOSCO Assessment Methodology had been developed. From the perspective of the IOSCO Principles, this is therefore effectively a first assessment. Hence, comparisons with the prior assessment are discouraged since the process has since been refined to promote consistency and has become progressively more rigorous. The assessment was based on: (i) a self-assessment and additional written responses prepared by the authorities; (ii) reviews of the relevant legislation and regulations; (iii) meetings with the management and staff of the FSC, SFC, FSS, Ministry of Strategy and Finance (MOSF), Bank of Korea (BOK), Seoul Central District Public Prosecutor s Office; and (iv) meetings with SROs and market participants, including the KRX, Korea Securities Depository (KSD), KOFIA, KICPA, Korean Chamber of Commerce and Industry, banks, securities companies, fund managers, issuers, credit rating agencies, audit firms and local lawyers specialized in securities markets law.